PERAN ORANG TUA DALAM MEMBENTUK KARAKTER RILIGIUS ANAK DI LINGKUNGAN MASYARAKAT NON MUSLIM (Studi kasus di Desa Dulitukan Kabupaten Lembata) - Ina Fatamala Making; Muhammad Fahmi Hidayatullah; Moh. Eko Nasrulloh (VICRATINA, 2022)
Education is a milestone in the progress of character and personality formation, is a primary human need to improve its characteristics and potential. Education at school and at home is important in non-formal education, namely education in the family. The family is the first place for children to receive education and is the basic foundation for the formation of character and personality. Therefore, parents must be able to educate their children. In daily life, children are influenced by the surrounding environment, both in terms of association and family conditions, which do not pay attention to the growth and development of children to the point of fostering the religious character of children. However, the understanding of parents Regency who facilitates or finances children to schools or madrasas related to education and religious understanding is only seen as a formal matter and merely fulfilling obligations but as parents paying special attention to children in terms of substance is very minimal. This research was conducted using a qualitative approach. Data were collected using in-depth interviews, participant observation and documentation. Then, the data analysis method uses the Miles and Hubberman method. The results of the research are that parents or families have a very strategic responsibility in the formation of children's religious character. Therefore, all parental behavior, both mothers and fathers, must reflect good behavior that can be used as role models for children, including: manners of speaking, how to dress, neighborly ways of life and other things that can please the heart and feelings such as: attention, affection, providing a comfortable life for children. Giving motivation in goodness and provide good advice for the benefit and happiness of children in the future. The role of parents in the formation of the religious character of children in Dulicu Village, especially in RT 10 RW 05 has been very good, and the religious character of children in Dulicukan Village is also better than before.Â Kata Kunci: Religiou Characters, Parents,Children